Nonbacterial and bacterial osteomyelitis in children: a case–control retrospective study - Kostik, Mikhail M.; Maletin, Alexey S.; Petukhova, Veronika V.; Mushkin, Alexander Yu. (Frontiers in Pediatrics, 2023)
Purpose Osteomyelitis is a group of bone infectious (bacterial osteomyeilitis–BO) and non-infectious inflammatory diseases (non-bacterial osteomyelitis–NBO) with similar clinical, radiology and laboratory features. Many patients with NBO are misdiagnosed as BO and receive unnecessary antibiotics and surgery. Our study aimed to compare clinical, laboratory features of NBO and BO in children; to define key discriminative criteria and create NBO diagnostic score (NBODS). Methods: The retrospective multicenter cohort study included clinical, laboratory, and instrumental information about histologically confirmed NBO (n=91) and BO (n=31). The variables allowed to differentiate both conditions used to construct and validate the NBO DS. Results: The main differences between NBO and BO were: onset age 7.3 (2.5; 10.6) vs. 10.5 (6.5; 12.7) years (p=0.03), frequency of fever (34.1% vs. 90.6%, p=0.0000001), symptomatic arthritis (67% vs. 28.1%, p=0.0001), monofocal involvement (28.6% vs. 100%, p=0.0000001), spine (32% vs. 6%, p=0.004), femur (41% vs. 13%, p=0.004), foot bones (40% vs 13%, p=0.005), clavicula (11% vs. 0%, p=0.05), sternum (11% vs. 0%, p=0.039) involvement. Four criteria: CRP≤55 mg/l (56 points), multifocal involvement (27 points), femur involvement (17 points), and neutrophil bands≤220 cell/μl (15 points) were included in the NBO DS. The summa>17 points allowed to differentiate NBO from BO with a sensitivity of 89.0% and specificity of 96.9%. Conclusion: the diagnostic criteria may help in discrimination NBO and BO and avoid excessive antibacterial treatment and surgery.